3(-x-3)=4x+9-7x

Simple and best practice solution for 3(-x-3)=4x+9-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-x-3)=4x+9-7x equation:



3(-x-3)=4x+9-7x
We move all terms to the left:
3(-x-3)-(4x+9-7x)=0
We add all the numbers together, and all the variables
3(-1x-3)-(-3x+9)=0
We multiply parentheses
-3x-(-3x+9)-9=0
We get rid of parentheses
-3x+3x-9-9=0
We add all the numbers together, and all the variables
-18!=0
There is no solution for this equation

See similar equations:

| 3(-6+2j)=-2(2j-1) | | 1/2x-10=22 | | 2(3x+8)=-28+2 | | r+8.1=-3.9 | | 3+6d=7+6+8d | | 7+4y=-5,y= | | 8x−5=10x−7 | | 6z-3z-1=2z+7 | | 8x-5=10x-78x−5=10x−7 | | 11/5y-3=-2 | | 11-4x-7-6=6 | | 24=33+x | | 12x-15=3(2x+13) | | x+16+x=21 | | -2(8-3h)=2(-6+4h) | | 20x+16=21 | | -5(2+3x)-4x=28 | | |x+2|=|2x+6|+1 | | -8g-1=-9g+9 | | 3(r−6)=9 | | 5(4x+9)=-26+51 | | 2g+2.6=18.6 | | 7.2=0.2m | | 4x+8=−1x−9 | | -19x—34=55—x | | 2p-4.2=1.8 | | 6(2x+6)-5=-5 | | 8n-5-1=-15+9n | | m-5.2/3=2.7 | | 17x+3⋅(x-1)=57 | | 1/2(2/3e-3+2e)=-4(1/8e+1-e) | | 56s^{2}+31s+3=0 |

Equations solver categories